Genetic relationship among selected heat and drought tolerant bread wheat genotypes using SSR markers, agronomic traits and grain protein content. (2nd October 2020) - Thungo, Zamalotshwa; Shimelis, Hussein; Odindo, Alfred; Mashilo, Jacob; Shayanowako, Admire
ABSTRACT: Assessing the genetic variation and relationships present in crop germplasm is a pre-requisite for parental selection and breeding. The objective of this study was to determine the genetic relationships present among selected heat and drought tolerant wheat genotypes using simple sequence repeat (SSR) markers, agronomic traits and grain quality parameters to select desirable parents for breeding. Twenty-four agronomically selected wheat genotypes sourced from the International Maize and Wheat Improvement Centre (CIMMYT)'s heat and drought tolerance nursery and four local check varieties were genotyped using 12 selected polymorphic SSR markers. The test genotypes were phenotyped using yield and yield-component traits, and grain protein content (GPC) under non-stressed (NS) and drought-stressed (DS) conditions. Expected heterozygosity mean value of 0.58 indicated moderate genetic diversity for breeding. The studied wheat genotypes were delineated into six genetic groups using cluster analysis. Significant genotypic differences were observed for agronomic traits and GPC under NS and DS conditions. Genetically unrelated breeding parents including LM02, LM13, LM23, LM41, LM44, LM71, LM73 and LM75 were selected for population development and breeding for enhanced grain yield and protein content under heat and drought-stressed environments.